Integrating Total Quality Management with Islamic Values in Modern Islamic Education - Luthfiatul Udhma; Sri Minarti (Managere: Indonesian Journal of Educational Management, 2025)
This study discusses the integration of Total Quality Management (TQM) and Islamic values in modern Islamic educational institutions, focusing on how the quality management approach can improve academic quality while building the character of students. The main problem is the lack of a TQM implementation model that holistically integrates Islamic values, so Islamic education often only emphasizes administrative aspects without strengthening the spiritual and moral dimensions. This research uses a qualitative method with a case study approach, involving in-depth interviews, documentation, and field findings on various stakeholders such as school leaders, teachers, students, and education supervisors. The study results show that implementing TQM based on Islamic values can create an education system that excels academically and in character, as long as it is supported by Islamic leadership, stakeholder involvement, and a structured and sustainable implementation strategy. These findings confirm that the quality of Islamic education is measured not only by the results of exams but also by the formation of the character and spirituality of students. The implications of this study reinforce the importance of cross-element collaboration and sustainable adaptation in the quality management of Islamic education and provide a practical model for the development of value-based education policies and practices in the future.